Interpreting the self : autobiography in the Arabic literary tradition - Reynolds, Dwight Fletcher, 1956-; Brustad, Kristen (Berkeley : University of California Press, 2001)
Autobiography is a literary genre which Western scholarship has ascribed mostly to Europe and the West. Countering this assessment and presenting many little-known texts, this comprehensive work demonstrates the existence of a flourishing tradition in Arabic autobiography.
Preliminaries; CONTENTS; Acknowledgments; Introduction; 1. The Fallacy of Western Origins; 2. The Origins of Arabic Autobiography; 3. Toward a History of Arabic Autobiography; 4. Arabic Autobiography and the Literary Portrayal of the Self; Part II. Translations; Conclusion; Annotated Guide to Arabic Autobiographical Writings; Glossary; References; List of Contributors; Index.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Includes translated text from Arabic.
digitized
Print version record.
Keywords: Arabic literature -- History and criticism; Autobiography; Authors, Arab -- Biography -- History and criticism; Arabic literature -- Translations into English; Autobiographies as Topic; Littérature arabe -- Histoire et critique; Autobiographie; Écrivains arabes -- Biographies -- Histoire et critique; autobiography (genre); 18.72 classical Arabic language and literature; LITERARY CRITICISM -- African; LITERARY CRITICISM -- General; Arabic literature; Authors, Arab -- Biography; Autobiography; Arabisch; Autobiografie; Autobiografische Literatur; Geschichte; Literatur; Quelle; Aufsatzsammlung; Arabisch; Autobiografieën.; Arabic literature -- History and criticism; Autobiography; Authors, Arab -- Biography -- History and criticism; Arabic literature -- Translations into English; Arabisch; Autobiography; autobiographies (literary works); Autobiographies; Criticism, interpretation, etc; Translations; Autobiographies; Autobiographies